2000
DOI: 10.1046/j.1365-2230.2000.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of pemphigus vulgaris presenting as bilateral foot ulcers

Abstract: We describe an unusual presentation of pemphigus vulgaris, an autoimmune intraepidermal blistering skin disease associated with autoantibodies to the desmosome glycoprotein, desmoglein 3. A 60-year-old man presented with bilateral ulceration on the dorsum of the feet. These clinical features persisted for 4 months before more characteristic signs of pemphigus vulgaris, including mouth ulceration and skin erosions, developed. The atypical presentation led to a delay in diagnosis and initiation of the appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Periungual localization of pemphigus is rare [2,3,4,5,6,7]. It has been claimed that this complication occurs more frequently in eastern populations, as observed in our 2 cases.…”
Section: Commentssupporting
confidence: 62%
See 1 more Smart Citation
“…Periungual localization of pemphigus is rare [2,3,4,5,6,7]. It has been claimed that this complication occurs more frequently in eastern populations, as observed in our 2 cases.…”
Section: Commentssupporting
confidence: 62%
“…In our cases, the clinical presentation was striking with oral involvement and isolated periungual lesions. Out of the 25 cases of paronychial pemphigus reported in the literature, an oral localization was present in 21 patients (84% of the cases) [2,3,4,5,6,7]. In the series of Schlesinger et al [1], the presence of mucous membrane involvement was unfortunately not specified.…”
Section: Commentsmentioning
confidence: 99%
“…Back in 1976, a review of 107 consecutive cases of pemphigus demonstrated dapsone to be a useful adjuvant to systemic corticosteroids [10] . Since then, dapsone's efficacy as a steroid-sparing agent in the treatment of PV has been documented in several reports [11][12][13][14][15][16][17][18][19][20] . However, the current data are mainly based on small retrospective case series and reports.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Dapsone was used as monotherapy in six (16%) patients. There were 37 patients in 13 reports who were treated with dapsone.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…[8,9,11,[14][15][16]18] In three patients, prednisone was discontinued; in seven patients, the dose of prednisone prior to initiation of dapsone was reduced. [8,9,11,[14][15][16]18] In three patients, prednisone was discontinued; in seven patients, the dose of prednisone prior to initiation of dapsone was reduced.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%